An updated review of glucocorticoid-related adverse events in patients with rheumatoid arthritis. Issue 7 (3rd July 2019) - Luís, Mariana; Freitas, João; Costa, Flávio; Buttgereit, Frank; Boers, Maarten; JAP, Da Silva; Santiago, Tânia
ABSTRACT: Introduction : Glucocorticoids represent a cornerstone in the treatment of rheumatoid arthritis. Their effect as a disease-modifying treatment in rheumatoid arthritis is well established. Despite this, the risk of adverse events of glucocorticoids, especially in high doses and over a long time, is constantly highlighted. Data on the prevalence and impact of glucocorticoid-related adverse effects in rheumatoid arthritis is needed, therefore, to be regularly revisited. Areas covered : In this review, our primary aim was to provide an update of evidence from randomized controlled trials and observational cohort studies on the safety of glucocorticoid treatment in rheumatoid arthritis. Our secondary aim was to provide a critical overview of the concerns raised with both study designs – randomized clinical trials versus nonrandomized observational studies – regarding the assessment of the safety of glucocorticoids in rheumatoid arthritis. Expert opinion : In the meantime, adherence to recommendations and consensus on standardized methodologies for monitoring and reporting adverse events is essential to improve our knowledge and competence in the best management of glucocorticoids.